Transcriptional Profiling of CD8+ CMV-Specific T Cell Functional Subsets Obtained Using a Modified Method for Isolating High-Quality RNA From Fixed and Permeabilized Cells - Healy, Zachary R.; Weinhold, Kent J.; Murdoch, David M. (Frontiers in Immunology, 2020)
Previous studies suggest that the presence of antigen-specific polyfunctional T cells is correlated with improved pathogen clearance, disease control, and clinical outcomes; however, the molecular mechanisms responsible for the generation, function, and survival of polyfunctional T cells remain unknown. The study of polyfunctional T cells has been, in part, limited by the need for intracellular cytokine staining (ICS), necessitating fixation and cell membrane permeabilization that leads to unacceptable degradation of RNA. Adopting elements from prior research efforts, we developed and optimized a modified protocol for the isolation of high-quality RNA (i.e., RIN > 7) from primary human T cells following aldehyde-fixation, detergent-based permeabilization, intracellular cytokines staining, and sorting. This modified protocol utilizes an optimized combination of an RNase inhibitor and high-salt buffer that is cost-effective while maintaining the ability to identify and resolve cell populations for sorting. Overall, this protocol resulted in minimal loss of RNA integrity, quality, and quantity during cytoplasmic staining of cytokines and subsequent flourescence-activated cell sorting. Using this technique, we obtained the transcriptional profiles of functional subsets (i.e., non-functional, monofunctional, bifunctional, polyfunctional) of CMV-specific CD8+T cells. Our analyses demonstrated that these functional subsets are molecularly distinct, and that polyfunctional T cells are uniquely enriched for transcripts involved in viral response, cell survival, proliferation and metabolism when compared to monofunctional cells. Polyfunctional T cells demonstrate reduced activation-induced cell death and increased proliferation after antigen re-challenge. Further in silico analysis of transcriptional data suggested a critical role for STAT5 transcriptional activity in polyfunctional cell activation. Pharmacologic inhibition of STAT5 was associated with a significant reduction in polyfunctional cell cytokine expression and proliferation, demonstrating the requirement of STAT5 activity not only for proliferation and cell survival, but also cytokine expression. Finally, we confirmed this association between CMV-specific CD8+ polyfunctionality with STAT5 signaling in immunosuppressed transplant recipients using single cell transcriptomics, indicating these results may translate to this vulnerable population. Collectively, these results shed light on mechanisms governing polyfunctional T cell function and survival and may ultimately inform multiple areas of immunology, including but not limited to the development of new vaccines, CAR-T cell therapies, and adoptive T cell transfer.